2020
DOI: 10.1021/acsomega.0c00387
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Acetic Acid Effect on Carbon Steel Corrosion in CO2–H2S Medium: Mechanistic Reaction Pathway and Kinetics

Abstract: Potentiodynamic polarization and electrochemical impedance measurements were employed to investigate the effect of acetic acid on the anodic dissolution of carbon steel in a CO2–H2S solution. Both polarization and impedance results unveil that the dissolution rate of carbon steel first increases and then decreases with an increase in acetic acid concentration. At lower concentrations of acetic acid, the corrosion rate increases due to the increase in cathodic current density. While the decrease in corrosion ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, in electrochemical terms, few differences were observed between conditions at 90°C, C1 (0 ppm of HAc) and C3 (100 ppm of HAc), mainly in terms of capacitive behaviour and LPR corrosion rates. Some authors have reported that an inhibitive effect might be seen with low concentrations of HAc up to 100 ppm due to a reduction on the anodic current [21,22,34]. In some cases, it might happen even without any corrosion layer deposition on the working electrode surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, in electrochemical terms, few differences were observed between conditions at 90°C, C1 (0 ppm of HAc) and C3 (100 ppm of HAc), mainly in terms of capacitive behaviour and LPR corrosion rates. Some authors have reported that an inhibitive effect might be seen with low concentrations of HAc up to 100 ppm due to a reduction on the anodic current [21,22,34]. In some cases, it might happen even without any corrosion layer deposition on the working electrode surface.…”
Section: Discussionmentioning
confidence: 99%
“…Talukdar et al. showed that with the increase of acetic acid concentration in solution, the dissolution of carbon steel initially increases and then decreases, suggesting a complex role of acetate/acetic‐acid [12b] . A detailed understanding of surface adsorption properties of different carboxylic acids and associated anions will help us better understand their role in corrosion and corrosion inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the presence of acetic acid causes an increase in the corrosion rate because the corrosion product of iron acetate has greater solubility compared with iron bicarbonate. The studies of Talukdar et al [ 17 ] indicate that in a CO 2 -H 2 S solution, at lower concentrations of acetic acid, the corrosion rate of carbon steel increases, while at higher concentrations of acetic acid, the corrosion rate decreases but pitting corrosion is observed. This is because the presence of more H + ions, supplied by HAc, reduces the adsorption of H 2 S species on carbon steel, resulting in a lower anodic dissolution rate.…”
Section: Introductionmentioning
confidence: 99%